Study on the dynamic effects of plateau hypoxic and cold environment on the thermal adaptation of short-term sojourners in Xizang - Duan, Guannan; Song, Cong; Liu, Yanfeng; Fu, Zhiguo; Zhang, Cong; Han, Xu; Li, Yong; Zhou, Yong (Journal of thermal biology, 2024)
The plateau hypoxic environment can affect the thermoregulation process of the human body, and due to the different acclimatization ability to the hypoxic environment, the thermal requirements among the people who enter Xizang at different times may be different. Accordingly, this study aims to clarify how plateau hypoxic environments influence the physiological and subjective responses of people entering Xizang at different times. And field experiments were conducted in Xi'an and Lhasa, respectively, to compare the thermal responses and oxygen responses of the subjects under different temperature conditions on the plain, the first day of entering Xizang and the 15th day of entering Xizang. The results showed that under the hypoxic environment, the thermal sensation of the subjects decreased. With the extension of the time entering Xizang, the influence of the hypoxic environment on thermal comfort was gradually weakened, but under the low temperature environment, the effect of hypoxia on thermal response was not significantly reduced. The results of this study can help to reveal how plateau hypoxic environments affect human thermal comfort and provide a theoretical basis for the design of indoor thermal environment parameters suitable for sojourners entering Xizang at different times. •Combined effects of hypoxia and cold environment on thermal comfort was studied.•The hypoxic environment further decreases the thermal sensation at low temperature.•The plateau cold environment aggravate the hypoxia sensation of sojourners.•Plateau hypoxic environment change the thermal comfort requirements of sojourners.•With hypoxia acclimatization, the effect of hypoxia on thermal comfort diminishes.